2023
DOI: 10.3847/1538-4357/ad0036
|View full text |Cite
|
Sign up to set email alerts
|

Ejecta, Rings, and Dust in SN 1987A with JWST MIRI/MRS

O. C. Jones,
P. J. Kavanagh,
M. J. Barlow
et al.

Abstract: Supernova (SN) 1987A is the nearest supernova in ∼400 yr. Using the JWST MIRI Medium Resolution Spectrograph, we spatially resolved the ejecta, equatorial ring (ER), and outer rings in the mid-infrared 12,927 days (35.4 yr) after the explosion. The spectra are rich in line and dust continuum emission, both in the ejecta and the ring. The broad emission lines (280–380 km s−1 FWHM) that are seen from all singly-ionized species originate from the expanding ER, with properties consistent with dense post-shock cool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 93 publications
1
14
0
Order By: Relevance
“…For the F1000W and F1800W filters, emission lines make a negligible contribution (Table 1). The contributions of synchrotron and free-free emission are also small except perhaps at wavelengths shorter than 8 μm (Jones et al 2023). It would seem that the most likely explanation for the small discrepancy at the two longest wavelengths between the Imager filter fluxes and the equivalent MRS filter fluxes is a difference in the background estimation, given that background flux levels rise steeply to longer wavelengths.…”
Section: Imagesmentioning
confidence: 95%
See 4 more Smart Citations
“…For the F1000W and F1800W filters, emission lines make a negligible contribution (Table 1). The contributions of synchrotron and free-free emission are also small except perhaps at wavelengths shorter than 8 μm (Jones et al 2023). It would seem that the most likely explanation for the small discrepancy at the two longest wavelengths between the Imager filter fluxes and the equivalent MRS filter fluxes is a difference in the background estimation, given that background flux levels rise steeply to longer wavelengths.…”
Section: Imagesmentioning
confidence: 95%
“…In Figure 5 we have superimposed on our image obtained through the F2550W filter the contours of the [Fe II]λ25.99 μm line from the MRS data. The MRS data clearly showed that this prominent line is coming mostly from the inner ejecta and the ejecta close to the reverse shock (Jones et al 2023), while the dust which dominates the F2550W filter is from the ring. The Imager data, which have a spatial resolution ∼2 times better than the MRS data, confirm this conclusion, with the dust-dominated F2550W image showing a drop in emission inside the ER, whereas the [Fe II]λ25.99-dominated contours peak inside the ER.…”
Section: Imagesmentioning
confidence: 95%
See 3 more Smart Citations